Weryfikacja Doświadczalna Teorii Nośności Granicznej Ustrojów Płytowo-Żebrowych - M. Kwieciński (Engineering Transactions, 1961)
The object of the present work is to verify by experiment the results of the theoretical analysis of the state of destruction of ribbed plate structures which constitute bent elements of common usage in building. First, the general assumptions of the theory of limit load are recalled, followed by a brief account of the principles of limit analysis of ribbed plate structures. Square and rectangular plates with two pairs of edge ribs are considered in detail. The orthotropy of the plate is taken into consideration as well as the plastic non-homogeneity of the structure, of which the properties vary in a jump-like manner at the joints between the plate and the ribs. Next, the paper contains a description of the principles of the investigation, the construction of the models and a device enabling the realization of a uniform continuous load by means of compressed air. This is made possible by using a tightly fitting chamber in which air was compressed by means of a compressor. Next, the limit moment of the rib co-working with a definite region of the plate and constituting with it a monolithic structure is determined theoretically. The values of the plastic moduli of the rib and the plate taken separately are assumed to be known. After the experimental determination of these moduli two sets of structures, square and rectangular, were tested. Each set contained models with various indices of plastic rigidity of ribs. The values of the ultimate loads computed theoret- ically and obtained experimentally and the discrepancies are collated in tables. The paper ends with final conclusions.